Tetrakis[(4-methoxycarbonyl)anilinium] hexachloridostannate(IV) dichloride - Wenzhi Xiao; Ruiting Xue; Yansheng Yin (Acta Crystallographica Section E, 2011)
The asymmetric unit of the title compound, (C8H10NO2)4[SnCl6]Cl2, contains two (4-methoxycarbonyl)anilinium cations, one chloride anion and one half of a hexachloridostannate(IV) dianion situated on a twofold rotation axis. All aminium H atoms are involved in N—H...Cl hydrogen bonding, which consolidate the crystal packing along with weak C—H...O interactions.